Enhancement of snow albedo reduction and radiative forcing due to coated black carbon in snow - Pu, Wei; Shi, Tenglong; Cui, Jiecan; Chen, Yang; Zhou, Yue; Wang, Xin (The Cryosphere, 2021)
When black carbon (BC) is mixed internally with other atmospheric particles, the BC light absorption effect is enhanced. This study explicitly resolved the optical properties of coated BC in snow based on the core / shell Mie theory and the Snow, Ice, and Aerosol Radiative (SNICAR) model. Our results indicated that the BC coating effect enhances the reduction in snow albedo by a factor ranging from 1.1–1.8 for a nonabsorbing shell and 1.1–1.3 for an absorbing shell, depending on the BC concentration, snow grain radius, and core / shell ratio. We developed parameterizations of the BC coating effect for application to climate models, which provides a convenient way to accurately estimate the climate impact of BC in snow. Finally, based on a comprehensive set of in situ measurements across the Northern Hemisphere, we determined that the contribution of the BC coating effect to snow light absorption exceeds that of dust over northern China. Notably, high enhancements of snow albedo reduction due to the BC coating effect were found in the Arctic and Tibetan Plateau, suggesting a greater contribution of BC to the retreat of Arctic sea ice and Tibetan glaciers.